The molecular gas main sequence and Schmidt-Kennicutt relation are fundamental, the star-forming main sequence is a (useful) byproduct - Baker, William M.; Maiolino, Roberto; Belfiore, Francesco; Bluck, Asa F L; Curti, Mirko; Wylezalek, Dominika; Bertemes, Caroline; Bothwell, M S; Lin, Lihwai; Thorp, Mallory; Pan, Hsi-An (Monthly notices of the Royal Astronomical Society, 2023)
We investigate the relationship between the star formation rate (SFR), stellar mass (M*), and molecular gas mass (⁠MH2⁠) for local star-forming galaxies. We further investigate these relationships for high-z (z = 1–3) galaxies and for the hosts of a local sample of active galactic nuclei (AGN). We explore which of these dependencies are intrinsic and which are an indirect byproduct by employing partial correlation coefficients and random forest regression. We find that for local star-forming galaxies, high-z galaxies, and AGN host galaxies, the Schmidt–Kennicutt (SK) relation (between MH2 and SFR) and the molecular gas main sequence (MGMS; between MH2 and M*) are intrinsic primary relations, while the relationship between M* and SFR, i.e. the star-forming main sequence (SFMS), is an indirect byproduct of the former two. Hence the SFMS is not a fundamental scaling relation for local or high-z galaxies. We find evidence for both the evolution of the MGMS and SK relation over cosmic time, where, at a given stellar mass, the higher the redshift, the greater the molecular gas mass and the star formation efficiency. We offer a parametrization of both the MGMS and SK relation’s evolution with redshift, showing how they combine to form the observed evolution of the SFMS. In addition, we find that the local AGN host galaxies follow an AGN–MGMS relation (as well as an AGN–SK relation), where the MGMS is offset to lower MH2 for a given M* compared to local star-forming galaxies.
Veröffentlicht: 23. November 2022
Gesehen am 05.06.2023